Preface - Laura MUGNAI; Richard FALLOON (Phytopathologia Mediterranea, 2023)
The 60th Anniversary of the MPU was celebrated in April 2022, during the 14th MPU Congress in Limassol, Cyprus (AA.VV., 2022). This Special Section of the journal contains four papers from the Congress, including a current topic paper and three reviews. These papers outline modern challenges to plant protection in Mediterranean crops, continuing the long-established traditions of the MPU and Phytopathologia Mediterranea.